Significance of Fluid Regime and Wetted Area in Biofilm Reactors - Muslu, Yilmaz (Springer Science and Business Media LLC, 2002)
Mass transfer within microbial films was described using Monod-type biological kinetics in terms of properties of filter media and feed solution. The performance characteristics of a trickling filter were thus modeled. The model enables one to consider the effect of inlet substrate concentration and flow rate upon the removal efficiency. For this purpose a second-order partial differential equation describing the dispersion phenomena inside the liquid layer was solved under special boundary conditions and used to determine substrate flux into the biofilm. A uniform biofilm thickness was considered. The model is based on computer techniques and the numerical evaluation of the normalized biofilm mathematical model. A design procedure was also given to calculate biological filters. The numerical model was also applied to experimental data to demonstrate its validity.
Keywords: Bioreactors; Models, Statistical; Biofilms